História recente da educação sexual na escola e da sexualidade no contexto da realidade brasileira - Pinheiro, Vandira Maria dos Santos (Brazilian Journal of Sexually Transmitted Diseases, 1997)
This arcicle presenrs a panoramic view of sexual education at school and sexuality in the Brazilian way of life from 1960 to 1963 in a cultural and political context. lt is aimed at making reflections on the rnrren t ídeology in educacional laws, which advocates che inclusion of themes such as sexuality and sexual trend on curricu/a. The author refers to laws and general directives, as well as to drawbacks in this copie. This material is aimed at healrh and education providers, sexuality researchers, counselors and others. as a basis to pedagogical pracrices in the public heafrh sector.